Freedom and Grace in the Teaching of Mark the Hermit - Czyżewski, Bogdan (Collectanea Theologica, 2021)
Mark the Hermit is one of the most important theoreticians of ascetic life in the ancient Church. In his ascetic writings, he takes up a number of subjects, including teaching about freedom and grace. This is not a systematic doctrine, but rather statements scattered in his works, occasional, often similar to each other. “Freedom” is defined by St. Mark the Hermit by the term ἐλευθερία, while “grace” – by the term χάρις. He also reminds us that freedom is given to man by Christ; man also receives it in the sacrament of baptism, because it frees him from the burden of sin. Grace, in turn, is presented by Mark the Hermit always as a gift from God given to man. Therefore, the Kingdom of Heaven is a gift, and not a reward for deeds, and the salvation that we receive from Christ is also grace. St Mark the Hermit’s teaching on freedom and grace certainly differs from the views of the Messalian sect, whose followers did not want to admit that grace and freedom are given to the baptised, so that they can perfect themselves throughout their lives and become similar to God.